Mechanical properties and residual stresses in cold-rolled aluminium channel sections. (15th November 2019) - Huynh, Le Anh Thi; Pham, Cao Hung; Rasmussen, Kim J.R.
Highlights: An experimental program of cold-rolled aluminium alloy 5052-H36 channel sections is performed. Energy dispersive X-ray spectroscopy technique is conducted for the chemical compositions. Flat and corner tensile coupon tests are performed in cold-rolled aluminium channels. New equations for corner properties of cold-rolled aluminium sections are proposed. Residual stress measurements throughout cold-rolled aluminium C-sections are performed. Abstract: In recent years, aluminium alloys have been paid more attention in the construction industry due to their attractive attributes such as light mass, high strength, easy recycling and high corrosion resistance. Traditionally, aluminium alloy sections used for structural applications have been formed by extrusion. Until recently, structural aluminium C- and Z- sections have been successfully cold-rolled from aluminium coil using existing rolling systems for cold-formed steel sections. During the cold-rolling process, plastic deformation at the corner regions results in strain hardening and associated enhancement of the yield stress. Also, the cold-rolling process may generate residual stresses around the cross-sections affecting the structural behaviour of members. It is therefore necessary to determine the mechanical properties and residual stresses caused by the cold-forming process. This paper describes an experimental program carried out at the University of Sydney to thoroughly investigate the distributions of mechanical properties and residual stresses throughout the cross-sections of cold-rolled aluminium C-sections. The experimental results provide an understanding of the magnitude and distribution of mechanical properties and residual stresses in cold-rolled aluminium sections, which are found to be different from those in cold-rolled steel and stainless-steel sections. Based on the experimental findings, the longitudinal membrane residual stresses are very small up to approximately 3% of yield stresses and may be neglected, whereas the longitudinal bending residual stresses are measured up to 30% of yield stresses.